Feed fortification with Psidium guajava (guava) as preventive treatment against vibriosis. - Dayaday, Katherine Labanza
The of apple guava (Psidium guajava) were tested for its efficacy as a preventive treatment against Vibrio harveyi infection by incorporating the powdered in commercial feed. Percent survival and the level of infection in Penaeus monodon after forty-eight hours of infection to V. harveyi-infected water indicated its effectiveness. The non-fortified feed showed the highest mortality (36.7 percent) after forty-eight hours of infection. Feed with chloramphen